2004
DOI: 10.1105/tpc.104.023945
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Novel Cell Signaling Role for Extracellular Adenosine Triphosphates and Diphosphates in Arabidopsis

Abstract: Extracellular ATP is a known receptor agonist in animals and was previously shown to alter plant growth, and so we investigated whether ATP derivatives could function outside plant cells as signaling agents. Signaling responses induced by exogenous nucleotides in animal cells typically include increases in free cytoplasmic calcium concentration ([Ca 2þ ] cyt ). We have evaluated the ability of exogenously applied adenosine 59-[g-thio]triphosphate (ATPgS), adenosine 59-[b-thio]diphosphate (ADPbS), and adenosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
236
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(246 citation statements)
references
References 59 publications
9
236
0
1
Order By: Relevance
“…1). In contrast to previous studies with Glu and ATP, which relied mostly on luminescence-based [Ca 2+ ] cyt measurements with aequorin-expressing plant cells (Dennison and Spalding, 2000;Demidchik et al, 2003;Jeter et al, 2004;Qi et al, 2006), the improved spatial resolution of FRETbased confocal imaging of YC3.60 allowed us to define regions of the root from which a particular [Ca 2+ ] cyt response originated. In doing so, we showed that all developmental regions of the root exhibited a [Ca 2+ ] cyt response to Glu and ATP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). In contrast to previous studies with Glu and ATP, which relied mostly on luminescence-based [Ca 2+ ] cyt measurements with aequorin-expressing plant cells (Dennison and Spalding, 2000;Demidchik et al, 2003;Jeter et al, 2004;Qi et al, 2006), the improved spatial resolution of FRETbased confocal imaging of YC3.60 allowed us to define regions of the root from which a particular [Ca 2+ ] cyt response originated. In doing so, we showed that all developmental regions of the root exhibited a [Ca 2+ ] cyt response to Glu and ATP.…”
Section: Discussionmentioning
confidence: 99%
“…Since ATP has been shown to induce [Ca 2+ ] cyt increases in plants using methods such as aequorin (Demidchik et al, 2003;Jeter et al, 2004) (Fig. 1B), the ATP-induced increase in [Ca 2+ ]cyt was generally followed by a more gradual decline that spanned a period of approximately 3 to 5 min (Fig.…”
Section: Fret-sensitized Emissionmentioning
confidence: 99%
“…For experiments measuring the [ATP] of the PGM, aliquots (30 mL) of medium were removed at 1 and 15 min after the treatments were applied, immediately placed in 1.5-mL graduated plastic vials, labeled, sealed, and frozen in liquid nitrogen until they were analyzed for ATP concentration as described by Jeter et al (2004).…”
Section: Assays Of In Vitro Pollen Growth and Atp Level In Growth Mediummentioning
confidence: 99%
“…For pollen growth experiments in which the volume of growth medium applied was 150 mL, the [eATP] in the medium was measured by luciferin-luciferase assay (Jeter et al, 2004) at 1 min after it was placed over the germinated grains and then again at 15 min after being applied. In all trials, the [eATP] of the medium rose between the first and second measurements and these increases were normalized for all experiments by expressing them as fold increases between the first and second time points assayed.…”
Section: Inhibition Of Apyrase Activity In Pollen Tubes Inhibits Theimentioning
confidence: 99%
See 1 more Smart Citation